Influence of altered geometry and material properties on tissue stress distribution under load in tendinopathic Achilles tendons – A subject-specific finite element analysis - Shim, Vickie B.; Hansen, Wencke; Newsham-West, Richard; Nuri, Leila; Obst, Steven; Pizzolato, Claudio; Lloyd, David G.; Barrett, Rod S. (Journal of biomechanics, 2019)
Achilles tendon material properties and geometry are altered in Achilles tendinopathy. The purpose of this study was to determine the relative contributions of altered material properties and geometry to free Achilles tendon stress distribution during a sub-maximal contraction in tendinopathic relative to healthy tendons. Tendinopathic (n = 8) and healthy tendons (n = 8) were imaged at rest and during a sub-maximal voluntary isometric contraction using three-dimensional freehand ultrasound. Images were manually segmented and used to create subject-specific finite element models. The resting cross-sectional area of the free tendon was on average 31% greater for the tendinopathic compared to healthy tendons. Material properties for each tendon were determined using a numerical parameter optimisation approach that minimised the difference in experimentally measured longitudinal strain and the strain predicted by the finite element model under submaximal loading conditions for each tendon. The mean Young’s modulus for tendinopathic tendons was 53% lower than the corresponding control value. Finite element analyses revealed that tendinopathic tendons experience 24% less stress under the same submaximal external loading conditions compared to healthy tendons. The lower tendon stress in tendinopathy was due to a greater influence of tendon cross-sectional area, which alone reduced tendon stress by 30%, compared to a lower Young’s modulus, which alone increased tendon stress by 8%. These findings suggest that the greater tendon cross-sectional area observed in tendinopathy compensates for the substantially lower Young’s modulus, thereby protecting pathological tendon against excessive stress.